Spring chicken [large type] : stay young forever (or die trying) - Gifford, Bill (Journalist) (Thorndike large print senior lifestyles series., 2015)
Spring Chicken examines the latest research, popular mythology, and ancient wisdom on mankind's oldest obsession: How can we live longer? And better? Reporter Bill Gifford takes readers on a journey through the science of aging, from the obvious signs like wrinkles and baldness right down into the innermost workings of cells. We visit cutting-edge labs where scientists are working to "hack" the aging process, like purging "senescent" cells from mice to reverse the effects of aging. He'll reveal why some people live past 100 without even trying, what has happened with resveratrol, the "red wine pill" that made headlines a few years ago, how your fat tissue is trying to kill you, and how it's possible to unlock longevity-promoting pathways that are programmed into our very genes. Gifford separates the wheat from the chaff as he exposes hoaxes and scams foisted upon an aging society, and arms readers with the best possible advice on what to do, what not to do, and what life-changing treatments may be right around the corner.